Development of Novel pH-Sensitive Eudragit Coated Beads Containing Curcumin-Mesalamine Combination for Colon-Specific Drug Delivery - Eman J. Heikal; Rashad M. Kaoud; Shadeed Gad; Hatem I. Mokhtar; Abdullah Alattar; Reem Alshaman; Sawsan A. Zaitone; Yasser M. Moustafa; Taha M. Hammady (Gels, 2023)
This research aims to develop a drug delivery system that effectively treats colitis while administering curcumin/mesalamine by coating alginate/chitosan beads with Eudragit® S-100 to target the colon. Beads were tested to determine their physicochemical characteristics. Coating with Eudragit® S-100 prevents drug release at a pH of less than 7; this was demonstrated by in-vitro release conducted in a medium with gradually varying pH to mimic circumstances in various regions of the gastrointestinal tract. This study examined the efficacy of the coated beads in treating acetic acid-induced colitis in rats. Results showed that spherical beads were formed with an average diameter of 1.6–2.8 mm, and the obtained swelling ranged from 409.80% to 890.19%. The calculated entrapment efficiency ranged from 87.49% to 97.89%. The optimized formula F13 (which was composed of mesalamine-curcumin active ingredients, Sodium alginate as a gelling agent, chitosan as a controlled release agent, CaCl2 as a crosslinking agent, and Eudragit S-100 as a pH-sensitive coating agent) demonstrated the best entrapment efficiency (97.89% ± 1.66), swelling (890.19% ± 60.1), and bead size (2.7 ± 0.62 mm). In formulation #13, which was coated with Eudragit S 100, curcumin (6.01 ± 0.04%) and mesalamine (8.64 ± 0.7%), were released after 2 h at pH 1.2; 6.36 ± 0.11% and 10.45 ± 1.52% of curcumin and mesalamine, respectively, were then released after 4 h and at pH 6.8. Meanwhile, at pH 7.4, after 24 h, approximately 85.34 ± 2.3% (curcumin) and 91.5 ± 1.2% (mesalamine) were released. Formula #13 significantly reduced the colitis, and this suggests that the developed hydrogel beads can be used for delivering curcumin-mesalamine combinations to treat ulcerative colitis after adequate research.